Práticas Criativas a partir de Microcervejarias Inovadoras de Minas Gerais - Ulisses Barros de Abreu Maia (2020)
Craft breweries are a recent and relevant phenomenon in the brazilian beverage food market due to the extraordinary capacity for innovation. Generally organized in small companies, craft breweries are recognized as innovative organizations, which have a continuous market growth, even in the face of the economic and financial downturn that Brazil has faced since 2014. However, remaining innovative and creative in this market represents a challenge, given the challenges in developing new quality products, with differentials that respond to the desires of a demanding consumer market, and the imposed economic limitations aforementioned. Based on observations and analysis derived from case studies of renowned creative microbreweries, the thesis defended in this study conceived that the exercise of creativity is a comprehensive activity, which is presented in several paths and strategies to solve the limitations that beer culture imposes on them. To better understand this phenomenon, qualitative methodologies were used, such as ethnography, grounded data theory, participant observation and analysis of the course of action on real or reconstituted situations of the creative processes experienced by master brewers within microbreweries. This research identified that microbreweries use specific thematic axes as innovation strategies, from different sources of creativity and trajectories when conceiving new creative products and services. This study builds a framework of creative practices showcasing the development in the classification of creative sources, in the characterization of strategies and in the analysis of the participation of actors in the beer culture. Analyzing cases of microbreweries in which creative solutions were reached in organizational forms, as well in products and services. These cases enabled the creation of a framework of creative practices towards innovation and discussions about the need for a more comprehensive understanding of the limitations imposed on producers and the participation of these actors in the beer culture, and also in the development of a better collective organization, aimed at improving the creative work on the part of microbreweries. In conclusion, the thesis presents the following academic and social contributions: the creation of a creativity framework for beer producers; a critical analysis of the development of a beer style precursing a future Brazilian beer school; and the socially impacting consolidation of a multi-media center focused on the development of beer technology in the Jequitinhonha Valley region in Minas Gerais.